Assessment of particulate PAHs toxicity from alcohol-diesel blends fuelled high compression ratio CI engine - Tomesh Kumar Sahu; Pravesh Chandra Shukla; Arindam Mondal; Satyajit Gupta; Giacomo Belgiorno; Gabriele Di Blasio (Cleaner Engineering and Technology, 2024)
Transport and power generation applications will play an important role in current and next-generation compression ignition (CI) engines. Methanol, ethanol, and butanol have emerged as potential alternative fuels for internal combustion engines capable of reducing overall greenhouse gases (GHG) and pollutant emissions. This study deals with the morphological characterization of particulate matter (PM) and toxicity assessment of polycyclic aromatic hydrocarbons (PAHs) for methanol, ethanol and butanol blending with diesel, and provides new findings and results in the specific literature. It defines new limits of alcohol fractions in diesel blends for their applications in CI engines. For the experimental assessment, a single-cylinder CI engine was used with an increased compression ratio (CR) from 17.5 to 26. Alcohol fraction of 20% (v/v) in diesel reduced the PM emissions in the range of 29–38% than diesel. PM was further reduced, up to ∼50%, for higher ethanol and butanol fractions (∼50%), and the soot morphological characteristics exhibit smaller particle sizes (400–600 nm) than diesel (up to 2 μm). Moreover, 20% of alcohol fraction led to a 34–60% reduction in PAHs. The toxicity evaluation of the tested alcohol-diesel blend indicates that high molecular weight PAHs and nitro-PAHs are the main contributors to the overall toxicity. Benzo[a]pyrene and dibenzo-anthracene were the prominent PAHs. Increasing the alcohol blend ratio significantly reduced the toxicity potential, ranging from 20 to 67%.